m^4-18m^2+81n^4 factorise
Answers
Answered by
3
she d d fjoa y to you later
Attachments:
![](https://hi-static.z-dn.net/files/d99/fa1947300b1f29e14bbfebd1b39516aa.jpg)
Answered by
12
Factorisation,
We have,
![{m}^{4} - 18 {n}^{2} {m}^{2} + 81 {n}^{4} {m}^{4} - 18 {n}^{2} {m}^{2} + 81 {n}^{4}](https://tex.z-dn.net/?f=+%7Bm%7D%5E%7B4%7D+-+18+%7Bn%7D%5E%7B2%7D+%7Bm%7D%5E%7B2%7D+%2B+81+%7Bn%7D%5E%7B4%7D+)
= m⁴ - 9m².n²- 9m².n²+ 81n⁴
= m²(m²- 9n²) - 9n²(m²-9n²)
= (m²-9n²)(m²- 9n²)
= {m²- (3n)²}{m²- (3n)²}
= (m + 3n)(m - 3n)(m + 3n)(m - 3n)
Or you can do it in this way,
Using the formula,a²-2ab+b² = (a-b)²
ok,
Now,
![{m}^{4} - 18 {n}^{2} {m}^{2} + 81 {n}^{4} {m}^{4} - 18 {n}^{2} {m}^{2} + 81 {n}^{4}](https://tex.z-dn.net/?f=+%7Bm%7D%5E%7B4%7D+-+18+%7Bn%7D%5E%7B2%7D+%7Bm%7D%5E%7B2%7D+%2B+81+%7Bn%7D%5E%7B4%7D+)
= (m²)²-2×9n×m + (9n²)²
= (m²- 9n²)²
= (m²-9n²)(m²- 9n²)
= {m²- (3n)²}{m²- (3n)²}
= (m + 3n)(m - 3n)(m + 3n)(m - 3n)
That's it
Hope it helped ^_^
We have,
= m⁴ - 9m².n²- 9m².n²+ 81n⁴
= m²(m²- 9n²) - 9n²(m²-9n²)
= (m²-9n²)(m²- 9n²)
= {m²- (3n)²}{m²- (3n)²}
= (m + 3n)(m - 3n)(m + 3n)(m - 3n)
Or you can do it in this way,
Using the formula,a²-2ab+b² = (a-b)²
ok,
Now,
= (m²)²-2×9n×m + (9n²)²
= (m²- 9n²)²
= (m²-9n²)(m²- 9n²)
= {m²- (3n)²}{m²- (3n)²}
= (m + 3n)(m - 3n)(m + 3n)(m - 3n)
That's it
Hope it helped ^_^
Similar questions
Chemistry,
9 months ago
English,
9 months ago
Math,
9 months ago
Math,
1 year ago
Computer Science,
1 year ago